LA PODEROSA THEMIS Y LA GALERÍA FÚNEBRE: UNA POLÉMICA EN PRENSA EN EL CONTEXTO DE LA TRADUCCIÓN DE COLECCIONES DE RELATOS EN ESPAÑA (1830-1831) - Alonso Seoane, María José (Anales de Filología Francesa, 2007)
By means of a letter of protest sent by Julián Anento and Basilio S. Castilians to El Correo Literario y Mercantil in July, 1831, on the publication of Galería fúnebre by Agustín Pérez Zaragoza, and his reply in the same newspaper, one can appreciate the common identity of the original French author (J. - P. - R. - Cuisin) and different aspects of interest, in order to know the state of the art on translation in Spain in the final years of Fernando VII’s reign, particularly regarding the relationship between literature and journalism of that period.